Godność małżeństwa - Kowal, Janusz (Horyzonty Wychowania, 2017)
In spite of the very difficult and complex situation of marriage and family in contemporary world, its negative image appears very one-sided, because there are also positive aspects of this situation. The changes which have taken place and are present in contemporary world point to a more distinctly genuine and positive character of the institution of marriage. One of the areas where these changes have occurred more broadly include the widespread model of monogamous marriage and conjugal laws which take into consideration the equality of women’s rights and the freedom of choice of the spouse. Even Muslim countries have experienced these changes; e.g. some of them introduced in the last century such marital regulations, which are all the more in conformity with the natural and evangelical values of the institution of marriage and the dignity of the human person. The changes in contemporary world are also reflected in the current legislation of the Catholic Church. Some newer norms protect, better than their predecessor did, the freedom of the parties contracting marriage and assure great protection against deceit or a conditioned act of the will for marriage. These examples bear witness to an ever greater esteem for the institution of marriage itself, as well as to the protection of the dignity of the persons who get married. The norms concerning the consummation of marriage and individual regulations showing „the favour of law” which marriage enjoys in the Catholic Church bear similar witness.